2016
DOI: 10.1155/2016/6320586
|View full text |Cite
|
Sign up to set email alerts
|

Protection Efficacy of the Extract of Ginkgo biloba against the Learning and Memory Damage of Rats under Repeated High Sustained +Gz Exposure

Abstract: Repeated high sustained positive Gz (+Gz) exposures are known for the harmful pathophysiological impact on the brain of rats, which is reflected as the interruption of normal performance of learning and memory. Interestingly, extract of Ginkgo biloba (EGb) has been reported to have neuroprotective effects and cognition-enhancing effects. In this study, we are interested in evaluating the protective effects of EGb toward the learning and memory abilities. Morris Water Maze Test (MWM) was used to evaluate the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 69 publications
1
11
0
Order By: Relevance
“…Since natural antioxidants are an essential component of health and might prevent or delay cell damage [ 20 ], they have been exploited as potential leads for the development of novel AD drugs [ 21 , 22 ]. Furthermore, the neuroprotective effects of natural antioxidants and nootropics [ 23 ], such as Ginkgo biloba [ 24 ] and Bacopa monnieri [ 25 ] have attracted considerable attention in the management of AD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since natural antioxidants are an essential component of health and might prevent or delay cell damage [ 20 ], they have been exploited as potential leads for the development of novel AD drugs [ 21 , 22 ]. Furthermore, the neuroprotective effects of natural antioxidants and nootropics [ 23 ], such as Ginkgo biloba [ 24 ] and Bacopa monnieri [ 25 ] have attracted considerable attention in the management of AD [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The greatest origin of natural antioxidant is medicinal plants. The neuroprotective effects of natural antioxidants and nootrpics, such as Ginkgo biloba, [40] Bacopa monnieri [41] and Huperzia serrata has [42] attained considerable attention in the management of AD.…”
Section: Introductionmentioning
confidence: 99%
“…[ 44 , 45 ] At the same time, it can scavenge free radicals and exert antioxidant properties. [ 18 ] The clinical application of EGb has been found to have significant effects on schizophrenia, depression and Alzheimer's disease. [ 23 , 46 , 47 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The main pharmacological action of EGb for the central nervous system is to inhibit platelet activating factor (PAF), promote blood circulation, increase blood flow, improve hemorheological changes, resist free radicals, increase tolerance to hypoxia, prevent brain edema induced by trauma and toxin, and protect nerves. [ 18 21 ] Recent studies have shown that EGb can improve the cognitive function of attention and memory in patients with mild to moderate Alzheimer's disease, and its curative effect is similar to that of Donepezil (cholinesterase inhibitor). [ 22 24 ]…”
Section: Introductionmentioning
confidence: 99%